The true art of the tax deal: Evidence of aid flows and bilateral double tax agreements - Julia Braun; Martin Zagler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Nash bargaining model shows that a deal is struck only if both countries mutually benefit. The model predicts voluntary signature of asymmetric double tax agreements only if there is compensation for the capital importer. Empirical evidence indicates that foreign aid from the capital exporter to the capital importer increases on average by 6 million USD In the signature year of a double tax agreement
Keywords: H2; 330